Frequency of repositioning for preventing pressure ulcers in patients hospitalized in ICU: protocol of a cluster randomized controlled trial - Olga L. Cortés; Mauricio Herrera-Galindo; Juan Carlos Villar; Yudi A. Rojas; María del Pilar Paipa; Luzdary Salazar (BMC, 2021)
Abstract Background Despite being considered preventable, ulcers due to pressure affect between 30 and 50% of patients at high and very high risk and susceptibility, especially those hospitalized under critical care. Despite a lack of evidence over the efficacy in prevention against ulcers due to pressure, hourly repositioning in critical care as an intervention is used with more or less frequency to alleviate pressure on patients' tissues. This brings up the objective of our study, which is to evaluate the efficacy in prevention of ulcers due to pressure acquired during hospitalization, specifically regarding two frequency levels of repositioning or manual posture switching in adults hospitalized in different intensive care units in different Colombian hospitals. Methods A nurse-applied cluster randomized controlled trial of parallel groups (two branches), in which 22 eligible ICUs (each consisting of 150 patients), will be randomized to a high-frequency level repositioning intervention or to a conventional care (control group). Patients will be followed until their exit from each cluster. The primary result of this study is originated by regarding pressure ulcers using clusters (number of first ulcers per patient, at the early stage of progression, first one acquired after admission for 1000 days). The secondary results include evaluating the risk index on the patients' level (Hazard ratio, 95% IC) and a description of repositioning complications. Two interim analyses will be performed through the course of this study. A statistical difference between the groups < 0.05 in the main outcome, the progression of ulcers due to pressure (best or worst outcome in the experimental group), will determine whether the study should be put to a halt/determine the termination of the study. Conclusion This study is innovative in its use of clusters to advance knowledge of the impact of repositioning as a prevention strategy against the appearance of ulcers caused by pressure in critical care patients. The resulting recommendations of this study can be used for future clinical practice guidelines in prevention and safety for patients at risk. Trial registration PENFUP phase-2 was Registered in Clinicaltrials.gov ( NCT04604665 ) in October 2020.